An intelligent pole-mounted circuit breaker shell surface treatment process and intelligent pole-mounted circuit breaker
Patent Information
- Application Number
- CN202611203542.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-13
AI Technical Summary
虽然外观平整光滑,但涂层与基材之间的结合力容易在冷热循环冲击下下降,造成起泡、脱落等现象,导致基体金属生锈
1、本申请在底层粉料的配方中,利用不同粒径的锌粉解决了传统单一粒径锌粉涂层致密度与粗糙度不可兼得的矛盾。在面层粉料配方中,引入聚四氟乙烯微球与纳米二氧化硅,与底层粉料协同构建表面微纳粗糙结构,配合氟硅烷助剂的低表面能修饰,使外壳表面接触角大幅提升,实现“荷叶效应”,使板材具备不易出现凝露,自清洁的功能。同时,通过220-245℃半固化与230-245℃终固化+急冷的温控曲线,既保证了层间分子的扩散与互锁,又通过急冷锁定了微纳形貌,防止高温下低表面能物质的回缩。因此,本申请通过底层粉料、面层粉料和工艺设计,实现了从物理屏蔽、电化学保护及表面能调控三个维度,全方位阻断了水汽与腐蚀介质的渗透路径,大幅度提高了板材的耐腐蚀性能。并且通过喷砂等操作,使板材表面粗糙度增大,能够提高与涂层之间的结合力。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to the technical field of circuit breakers, and in particular to a surface treatment process for the housing of an intelligent pole-mounted circuit breaker and the intelligent pole-mounted circuit breaker itself. Background Technology
[0002] Pole-mounted circuit breakers are critical switching devices installed on utility poles to control and protect overhead power distribution lines. Their primary function is to automatically disconnect the circuit in the event of overload, short circuit, or ground fault, ensuring the safe and stable operation of the power grid. Because pole-mounted circuit breakers are exposed to harsh outdoor environments for extended periods, their casings (usually box-like structures) are typically made of metal materials (such as Q235 carbon steel, stainless steel, or aluminum alloy). As a physical barrier for the internal vacuum interrupter, operating mechanism, and control circuitry, the metal casing must possess excellent corrosion resistance, weather resistance, and mechanical strength.
[0003] Currently, the industry mainly uses hot-dip galvanizing and powder coating / painting methods for surface treatment of metal sheets used in pole-mounted circuit breakers. Hot-dip galvanizing involves immersing rust-removed steel parts in molten zinc at approximately 500°C, causing a zinc layer to adhere to the workpiece surface. This process offers a long corrosion protection life, but suffers from uneven zinc layer thickness, rough surface, and susceptibility to drips and zinc nodules. Directly spraying epoxy resin or polyester powder coatings onto the metal surface produces a smooth appearance, but the adhesion between the coating and the substrate is easily weakened by thermal cycling, leading to blistering, peeling, and ultimately, rusting of the base metal. Therefore, further research is needed on the surface treatment of metal sheets used for circuit breaker housings. Summary of the Invention
[0004] In order to improve the corrosion resistance of the circuit breaker housing and the adhesion of the coating, and at the same time improve the corrosion resistance of the coating, this application provides a surface treatment process for the housing of an intelligent pole-mounted circuit breaker and an intelligent pole-mounted circuit breaker.
[0005] In a first aspect, this application provides a surface treatment process for the housing of an intelligent pole-mounted circuit breaker, employing the following technical solution: A surface treatment process for the housing of a smart pole-mounted circuit breaker includes the following steps: S1, Preprocessing Take the sheet material used for the casing of the steel column-mounted circuit breaker, degrease and dry it to obtain the pretreated sheet material; S2, Sandblasting The surface of the pre-treated board is sandblasted. S3, Preheating The sandblasted board is preheated to 120-150℃ to obtain a preheated board. S4, Apply primer powder Spray a base layer of powder with a thickness of 0.3-0.45mm onto the surface of the preheated plate. After spraying, keep it at a temperature of 220-245℃ for 3-8 minutes for semi-curing. The surface powder comprises the following raw materials in parts by weight: 55-65 parts of flake zinc powder with an average particle size of 10-20 μm, 15-25 parts of spherical zinc powder with an average particle size of 1-5 μm, 3-7 parts of nano zinc powder, 11-15 parts of bisphenol A type epoxy resin, 1.5-2.5 parts of phenolic curing agent, 0.2-0.6 parts of leveling agent, and 0.2-0.6 parts of silane coupling agent; S5, Topcoat Powder After the material has partially cured, a topcoat powder is sprayed onto the surface of the board. The surface powder comprises the following raw materials in parts by weight: 2-4 parts of polytetrafluoroethylene microspheres with an average particle size of 1-5 μm, 3-6 parts of nano-sized silica, 10-20 parts of precipitated barium sulfate with an average particle size of 1-5 μm, 70-80 parts of bisphenol A type epoxy resin, 9-12 parts of phenolic curing agent, and 0.5-1.3 parts of fluorosilane additive; S6, Curing and Cooling The plate with the sprayed surface powder is cured at 230-245℃ for 30-45 minutes, then removed and rapidly cooled to below 50℃ within 1.5-3 minutes, thus completing the surface treatment of the plate used for the pole-mounted circuit breaker housing.
[0006] By adopting the above technical solution, this application utilizes 10-20μm flake zinc powder in the formulation of the bottom layer powder to provide sacrificial anode protection and shielding, and 1-5μm spherical zinc powder to fill the gaps between the flakes. Nano-zinc powder is then used to construct a micro-nano transition layer, resolving the contradiction between density and roughness inherent in traditional single-particle-size zinc powder coatings. In the formulation of the top layer powder, polytetrafluoroethylene microspheres and nano-silica are introduced to synergistically construct a surface micro-nano rough structure with the bottom layer powder. Combined with the low surface energy modification of fluorosilane additives, the contact angle of the outer shell surface is significantly increased, achieving a "lotus effect," giving the board a self-cleaning function and preventing condensation. Simultaneously, the temperature control curve of 220-245℃ semi-curing and 230-245℃ final curing + rapid cooling ensures both the diffusion and interlocking of interlayer molecules and locks in the micro-nano morphology through rapid cooling, preventing the shrinkage of low surface energy materials at high temperatures. Therefore, this application, through the design of the base powder, top powder, and process, comprehensively blocks the penetration paths of water vapor and corrosive media from three dimensions: physical shielding, electrochemical protection, and surface energy regulation, significantly improving the corrosion resistance of the substrate. Furthermore, by using processes such as sandblasting, the surface roughness of the substrate is increased, which enhances the adhesion between the substrate and the coating.
[0007] Preferably, in step S5, the coating thickness of the surface powder is 0.15-0.3 mm.
[0008] Through practical application of the above technical solution, it was found that the coating thickness of the topcoat powder has a significant impact on the superhydrophobic properties of the coating surface. This also indirectly verifies that the micro / nano structure of the coating relies on the synergy between the topcoat and bottomcoat powders. If the thickness is too large (>0.3 mm), it will not only obscure the ability of the underlying micro / nano structure, leading to a decrease in the hydrophobicity of the coating, but also increase the risk of cracking due to increased internal stress. If the thickness is too small (<0.15 mm), a continuous insulating barrier cannot be formed, and the nanofillers are difficult to distribute uniformly. This thickness range ensures the effective prominence of the micro / nano structure on the coating surface, while meeting the electrical insulation strength requirements of the pole-mounted circuit breaker housing, preventing insufficient creepage distance or partial discharge due to an excessively thin coating.
[0009] Preferably, in S4 and S5, electrostatic spraying is used when spraying the base powder and the top powder.
[0010] By adopting the above technical solution, since the outer shell of pole-mounted circuit breakers typically has complex structures such as edges, flanges, and mounting holes, the edge effect generated by the electrostatic field can guide charged powder particles to adhere to these areas that are difficult to powder-coated. Compared with traditional air spraying, electrostatic spraying significantly improves the powder coating rate and deposition efficiency, ensures the uniformity of thickness between the base layer and the top layer in complex geometries, and eliminates the localized corrosion cell effect caused by uneven coating.
[0011] Preferably, in step S4, when spraying the base powder, the temperature of the substrate is maintained between 100-130°C.
[0012] By adopting the above technical solution, a certain preheating temperature can improve the adsorption of powder by the board, improve the adhesion of powder, and prevent interlayer delamination during subsequent mechanical vibration or hot and cold cycles.
[0013] Preferably, the fluorosilane additive is one or both of perfluorooctyltriethoxysilane and heptadecafluorodecyltrimethoxysilane.
[0014] By employing the above-mentioned technical solution, these additive molecules contain a hydrolyzable alkoxy group at one end, which can undergo a condensation reaction with the hydroxyl groups on the surface of nano-silica or resin to achieve chemical bonding; the other end contains a perfluoroalkyl chain (-CF3, -CF2-). During the curing process, these low surface energy perfluoro segments spontaneously migrate to the coating surface and align themselves to form a dense hydrophobic monolayer. This layer not only imparts superhydrophobicity to the surface but also possesses oleophobicity, effectively preventing the adhesion of oil and dust in outdoor environments and maintaining long-term anti-flashover performance.
[0015] Preferably, in step S2, the surface roughness of the pretreated plate after sandblasting is 6-10 μm.
[0016] By adopting the above technical solution, a suitable depth-to-width ratio anchor pattern is formed within this roughness range. The increase in roughness not only significantly increases the physical contact area, but also enhances the adhesion of the coating through van der Waals forces and mechanical interlocking forces.
[0017] Preferably, the preparation method of the bottom layer powder is as follows: After premixing flake zinc powder, spherical zinc powder, bisphenol A epoxy resin, phenolic curing agent, polyacrylate leveling agent and silane coupling agent, the mixture is transferred to a twin-screw extruder and the temperature is controlled at 110-125℃. After melt extrusion, the mixture is cooled and pressed into sheets with a thickness of 0.5-2mm. Before pulverization, nano zinc powder is added externally to the pulverizer, and the particle size is 10-40μm to obtain the bottom powder.
[0018] By adopting the above technical solution, a specific process of "melt extrusion + external addition of nano-zinc powder" is used. Conventional melt extrusion will cause the nano-zinc powder to agglomerate or be completely encapsulated by resin due to high temperature (110-125℃) and shear force, thus losing its nano-effect. Experiments have shown that adding it externally is more conducive to the dispersion of nano-zinc powder and the formation of micro-nano structures on the surface of the micro-coating.
[0019] Secondly, this application provides an intelligent pole-mounted circuit breaker, which adopts the following technical solution: A smart pole-mounted circuit breaker includes the following steps: the housing of the smart pole-mounted circuit breaker is made by a surface treatment process for the housing of the smart pole-mounted circuit breaker.
[0020] By adopting the above technical solution, this process endows the circuit breaker casing with the characteristics of "self-cleaning, water-repellent, and highly corrosion-resistant," directly reducing the risk of internal corrosion, short circuits in electronic components, and insulation failure caused by condensation, acid rain, and salt spray. For power grid equipment installed in the field, coastal areas, or highly polluted areas, it is beneficial to extend the operation and maintenance cycle (reducing the frequency of maintenance) and improve power supply reliability (reducing the failure trip rate).
[0021] In summary, this application includes at least one of the following beneficial technical effects: 1. This application resolves the inherent contradiction between density and roughness in traditional single-particle-size zinc powder coatings by utilizing zinc powders of varying particle sizes in the base layer powder formulation. In the top layer powder formulation, polytetrafluoroethylene microspheres and nano-silica are introduced to synergistically construct a micro-nano rough surface structure with the base layer powder. Combined with the low surface energy modification of fluorosilane additives, this significantly increases the contact angle of the outer shell surface, achieving a "lotus leaf effect" and enabling the board to resist condensation and possess self-cleaning properties. Simultaneously, a temperature control curve of 220-245℃ semi-curing and 230-245℃ final curing + rapid cooling ensures both the diffusion and interlocking of interlayer molecules and locks in the micro-nano morphology through rapid cooling, preventing the retraction of low surface energy materials at high temperatures. Therefore, this application, through the base layer powder, top layer powder, and process design, comprehensively blocks the penetration paths of water vapor and corrosive media from three dimensions: physical shielding, electrochemical protection, and surface energy regulation, significantly improving the corrosion resistance of the board. Furthermore, by performing operations such as sandblasting, the surface roughness of the board is increased, which can improve the adhesion between the board and the coating.
[0022] 2. Fluorosilane additives contain a hydrolyzable alkoxy group at one end of their molecules, which can undergo a condensation reaction with the hydroxyl groups on the surface of nano-silica or resin to achieve chemical bonding; the other end contains perfluoroalkyl chains (-CF3, -CF2-). During the curing process, these low surface energy perfluoro segments spontaneously migrate to the coating surface and align themselves to form a dense hydrophobic monolayer. This layer not only imparts superhydrophobicity to the surface but also possesses oleophobic properties, effectively preventing the adhesion of oil and dust in outdoor environments and maintaining long-term anti-flashover performance. Detailed Implementation
[0023] The following provides a more detailed description of this application in conjunction with specific details.
[0024] raw material All raw materials used in the preparation examples and embodiments of this application were purchased commercially. Among them, the bisphenol A type epoxy resin was purchased from Anhui Meijia New Materials, model E-12; the phenolic curing agent was purchased from Hunan Jiashengde Materials Technology, model PFNH-9080M; and the polyacrylate leveling agent was purchased from Aupur (Tianjin), model OPL-988.
[0025] Preparation Example Preparation Examples 1-3 A bottom powder, the raw materials and their amounts are shown in Table 1, and its preparation method is as follows: After premixing flake zinc powder, spherical zinc powder, bisphenol A epoxy resin, phenolic curing agent, polyacrylate leveling agent and silane coupling agent (KH550), the mixture is transferred to a twin-screw extruder and the temperature is controlled at 115℃. After melt extrusion, the mixture is cooled and pressed into sheets with a sheet thickness of 1.0 mm. Before pulverization, nano zinc powder is added externally to the pulverizer and the particle size is 30 μm to obtain the bottom layer powder.
[0026] Table 1. Raw materials and dosage (kg) of the bottom layer powders used in Examples 1-3
[0027] Preparation Example 4 A surface coating powder, the raw materials and their amounts are shown in Table 2, and its preparation method is as follows: 2.5 kg of micron-sized polytetrafluoroethylene microspheres (average particle size 1 μm), 4 kg of nano-sized silica (average particle size 40 nm), 15 kg of precipitated barium sulfate (average particle size 1 μm), 75 kg of bisphenol A type epoxy resin, 10 kg of phenolic curing agent, and 0.8 kg of fluorosilane additive (perfluorooctyltriethoxysilane) were mixed evenly and transferred to a twin-screw extruder. The temperature was controlled at 115℃. After melt extrusion, the mixture was cooled, pressed into sheets with a sheet thickness of 1.0 mm, and then pulverized to a particle size of 30 μm to obtain the surface powder. Example
[0028] Example 1 A surface treatment process for the housing of a smart pole-mounted circuit breaker includes the following steps: S1, Preprocessing Take the Q235 steel pole-mounted circuit breaker shell plate, perform alkaline degreasing, water washing, and drying to obtain pretreated plate; S2, Sandblasting Using 24-mesh brown fused alumina, with a pressure of 0.55MPa, an angle of 45°, and a spray distance of 200mm, the pre-treated plate was sandblasted to a surface roughness of 8μm. S3, Preheating The sandblasted board is placed in an oven and heated to 130°C. It is kept at this temperature for 10 minutes to obtain a preheated board. S4, Apply primer powder The preheated board was removed and electrostatically sprayed with a base layer powder at a voltage of 70kV. The spray thickness was controlled at 0.35mm. During the spraying process, the board temperature was maintained between 100-130℃. The board was then transferred to an oven, heated to 220℃, and held for 5 minutes. It was then removed and semi-cured. The base layer powder was prepared using the method described in Preparation Example 1. S5, Topcoat Powder The semi-cured board was electrostatically sprayed with a top layer powder, the thickness of which was controlled to be 0.15 mm; the top layer powder was prepared by the preparation method of Preparation Example 4. S6, Curing and Cooling Transfer the plate coated with the powder coating to an oven, heat it to 230°C, and cure it for 30 minutes. After removing it, use a strong cooling fan to rapidly cool it down to below 50°C within 2 minutes, thus completing the surface treatment of the plate for the pole-mounted circuit breaker housing.
[0029] Example 2 A surface treatment process for the housing of an intelligent pole-mounted circuit breaker differs from that of Example 1 in that the underlying powder is prepared by the preparation method of Example 2, while the remaining steps are the same as those of Example 1.
[0030] Example 3 A surface treatment process for the housing of an intelligent pole-mounted circuit breaker differs from that of Example 1 in that the underlying powder is prepared by the preparation method of Example 3, while the remaining steps are the same as those of Example 1.
[0031] Example 4 A surface treatment process for the housing of an intelligent pole-mounted circuit breaker differs from that in Example 2 in that the coating thickness of the surface powder in S5 is 0.2 mm, while the remaining steps are the same as in Example 2.
[0032] Example 5 A surface treatment process for the housing of an intelligent pole-mounted circuit breaker differs from that in Example 2 in that the coating thickness of the surface powder in S5 is 0.25 mm, while the remaining steps are the same as in Example 2.
[0033] Example 6 A surface treatment process for the housing of an intelligent pole-mounted circuit breaker differs from that in Example 2 in that the coating thickness of the surface powder in S5 is 0.3 mm, while the remaining steps are the same as in Example 2.
[0034] Example 7 A surface treatment process for the housing of a smart pole-mounted circuit breaker differs from that in Example 2 in that, during the preparation of the bottom powder, nano zinc powder is premixed with the other raw materials and then melt-extruded. The remaining steps are the same as in Example 2.
[0035] Comparative Example Comparative Example 1 A surface treatment process for the housing of an intelligent pole-mounted circuit breaker differs from that in Example 2 in that, in the bottom layer powder in S4, both spherical zinc powder and nano zinc powder are replaced with equal masses of flake zinc powder, while the remaining steps are the same as in Example 2.
[0036] Comparative Example 2 A surface treatment process for the housing of an intelligent pole-mounted circuit breaker differs from that in Example 2 in that the coating thickness of the surface powder in S5 is 0.4 mm, while the remaining steps are the same as in Example 2.
[0037] Comparative Example 3 A surface treatment process for the housing of an intelligent pole-mounted circuit breaker differs from that in Example 2 in that, in step S6, a strong cooling fan is not used for rapid cooling. After the cured board is taken out of the oven, it is naturally air-dried. The remaining steps are the same as in Example 2.
[0038] Performance testing Detection methods / test methods The surface treatment of the pole-mounted circuit breaker housing plates was carried out according to the surface treatment processes of Examples 1-7 and Comparative Examples 1-3, and then the following tests were performed on them. The test results are shown in Table 2.
[0039] Corrosion resistance test: The test shall be conducted by the neutral salt spray test in GB / T10125-2021, and the salt solution shall be a 5% sodium chloride solution by mass. Adhesion rating: Tested according to the test method in GB / T9286-2021.
[0040] Table 2. Detection results of Examples 1-7 and Comparative Examples 1-3
[0041] As can be seen from the test data in Table 2, the surface treatment process of the intelligent pole-mounted circuit breaker housing in this application enables the housing to have superhydrophobic properties, gives the plate surface self-cleaning properties, greatly improves the corrosion resistance of the plate, and the coating adhesion is good.
[0042] In conjunction with Examples 2 and 4-6, as well as Comparative Example 2, the coating thickness of the topcoat powder has a significant impact on the superhydrophobic properties of the coating surface. This also indirectly verifies that the micro / nano structure of the coating relies on the synergy between the topcoat powder and the bottomcoat powder. If the thickness is too large (>0.3 mm), it will not only obscure the ability of the micro / nano structure built in the bottom layer, leading to a decrease in the hydrophobicity of the coating, but also increase the risk of cracking due to increased internal stress in the coating. If the thickness is too small (<0.15 mm), a continuous insulating barrier cannot be formed, and the nanofillers are difficult to distribute uniformly. This thickness range ensures the effective prominence of the micro / nano structure on the coating surface, while meeting the electrical insulation strength requirements of the pole-mounted circuit breaker housing, preventing insufficient creepage distance or partial discharge due to an excessively thin coating.
[0043] Combining Examples 2 and 7, adding the zinc nanopowder externally is more conducive to the dispersion of the nano-zinc powder and the formation of the micro-nano structure on the surface of the micro-coating.
[0044] Combining Example 2 and Comparative Example 1, 10-20 μm flake zinc powder provides sacrificial anode protection and shielding, while 1-5 μm spherical zinc powder fills the gaps between the flakes. Nano-sized zinc powder is then used to construct a micro / nano transition layer, resolving the inherent trade-off between density and roughness in traditional single-particle-size zinc powder coatings. Single-particle-size zinc powder coatings struggle to form superhydrophobic micro / nano structures on the coating surface.
[0045] Combining Example 2 and Comparative Example 3, rapid cooling was used to lock the micro / nano morphology, preventing the retraction of low surface energy materials at high temperatures. This promotes the spontaneous migration and directional alignment of low surface energy perfluorinated segments to the coating surface, improving the superhydrophobicity of the coating surface.
[0046] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A surface treatment process for the housing of an intelligent pole-mounted circuit breaker, characterized in that: It includes the following steps: S1, Preprocessing Take the sheet material used for the casing of the steel column-mounted circuit breaker, degrease and dry it to obtain the pretreated sheet material; S2, Sandblasting The surface of the pre-treated board is sandblasted. S3, Preheating The sandblasted board is preheated to 120-150℃ to obtain a preheated board. S4, Apply primer powder Spray a base layer of powder with a thickness of 0.3-0.45mm onto the surface of the preheated plate. After spraying, keep it at a temperature of 220-245℃ for 3-8 minutes for semi-curing. The surface powder comprises the following raw materials in parts by weight: 55-65 parts of flake zinc powder with an average particle size of 10-20 μm, 15-25 parts of spherical zinc powder with an average particle size of 1-5 μm, 3-7 parts of nano zinc powder, 11-15 parts of bisphenol A type epoxy resin, 1.5-2.5 parts of phenolic curing agent, 0.2-0.6 parts of leveling agent, and 0.2-0.6 parts of silane coupling agent; S5, Topcoat Powder After the material has partially cured, a topcoat powder is sprayed onto the surface of the board. The surface powder comprises the following raw materials in parts by weight: 2-4 parts of polytetrafluoroethylene microspheres with an average particle size of 1-5 μm, 3-6 parts of nano-sized silica, 10-20 parts of precipitated barium sulfate with an average particle size of 1-5 μm, 70-80 parts of bisphenol A type epoxy resin, 9-12 parts of phenolic curing agent, and 0.5-1.3 parts of fluorosilane additive; S6, Curing and Cooling The plate with the sprayed surface powder is cured at 230-245℃ for 30-45 minutes, then removed and rapidly cooled to below 50℃ within 1.5-3 minutes, thus completing the surface treatment of the plate used for the pole-mounted circuit breaker housing.
2. The surface treatment process for the housing of an intelligent pole-mounted circuit breaker according to claim 1, characterized in that: In step S5, the coating thickness of the surface powder is 0.15-0.3 mm.
3. The surface treatment process for the housing of an intelligent pole-mounted circuit breaker according to claim 1, characterized in that: In S4 and S5, electrostatic spraying is used when spraying the base powder and the top powder.
4. The surface treatment process for the housing of an intelligent pole-mounted circuit breaker according to claim 1, characterized in that: In step S4, when spraying the base powder, the temperature of the substrate is maintained between 100-130°C.
5. The surface treatment process for the housing of an intelligent pole-mounted circuit breaker according to claim 1, characterized in that: The fluorosilane additive is one or both of perfluorooctyltriethoxysilane and heptadecafluorodecyltrimethoxysilane.
6. The surface treatment process for the housing of an intelligent pole-mounted circuit breaker according to claim 1, characterized in that: In step S2, the surface roughness of the pretreated plate after sandblasting is 6-10 μm.
7. The surface treatment process for the housing of an intelligent pole-mounted circuit breaker according to claim 1, characterized in that: The preparation method of the bottom layer powder is as follows: After premixing flake zinc powder, spherical zinc powder, bisphenol A epoxy resin, phenolic curing agent, polyacrylate leveling agent and silane coupling agent, the mixture is transferred to a twin-screw extruder and the temperature is controlled at 110-125℃. After melt extrusion, the mixture is cooled and pressed into sheets with a thickness of 0.5-2mm. Before pulverization, nano zinc powder is added externally to the pulverizer, and the particle size is 10-40μm to obtain the bottom powder.
8. A smart pole-mounted circuit breaker, characterized in that: The housing of the intelligent pole-mounted circuit breaker is made by a surface treatment process for the housing of an intelligent pole-mounted circuit breaker as described in any one of claims 1-7.